Zika Virus Transmission Through Blood Tissue Barriers - Khaiboullina, Svetlana F.; Ribeiro, Fabiola M.; Uppal, Timsy; Martynova, Ekaterina V.; Rizvanov, Albert A.; Verma, Subhash C. (Frontiers in Microbiology, 2019)
The recent Zika virus (ZIKV) epidemic in the Americas and the Caribbean revealed a new deadly strain of the mosquito-borne virus, which has never been associated with previous outbreaks in Asia. For the first time, widespread ZIKV infection was shown to cause microcephaly and death of newborns, which was most likely due to the mutation acquired during the large outbreak recorded in French Polynesia in 2013-2014. Productive ZIKV replication and persistence has been demonstrated in placenta and fetal brains. Possible association between ZIKV and microcephaly and fetal death has been confirmed using immunocompetent mouse models in vitro and in vivo. Having crossed the placenta, ZIKV directly targets neural progenitor cells (NPCs) in developing human fetus and triggers apoptosis. The embryonic endothelial cells are exceptionally susceptible to ZIKV infection, which causes cell death and tissue necrosis. On the contrary, ZIKV infection does not affect the adult brain microvascular cell morphology and blood-brain barrier function. ZIKV is transmitted primarily by Aedes mosquito bite and is introduced into the placenta/blood through replication at the site of the entry. Also, virus can be transmitted through unprotected sex. Although, multiple possible routes of virus infection have been identified, the exact mechanism(s) utilized by ZIKV to cross the placenta still remain largely unknown. In this review, the current understanding of ZIKV infection and transmission through the placental and brain barriers is summarized.